MOISTURE AND PH DETECTION USING SENSORS AND AUTOMATIC IRRIGATION SYSTEM USING RASPBERRY PI BASED IMAGE PROCESSING - Sagar, Shetty; Debjeet, Bardhan; Advait, Lokhande; Mishra, Nitish (International Journal of Engineering Technologies and Management Research, 2018)
India’s population rate is increasing day by day. In near future, we could face serious problem of food and other daily necessities, hence the development of agriculture is necessary. Today, the farmers are suffering due to inconsistent rains and scarcity of water. The main objective of this paper is to provide an automatic irrigation system, thereby saving their time, money & power of the farmer. The traditional farm-land irrigation techniques require manual intervention. With the automated technology of irrigation, the human intervention can be minimized. There will be moisture sensors installed on the field. Whenever there is a change in water content of soil these sensors sense the change gives an interrupt signal to the micro-controller. As soil is recognized as one of the most valuable natural resource whose pH property used to describe the degree of acidity or basicity which affect nutrient availability and ultimately plant growth. For capturing the images, a camera is used and after processing the captured image the pH value of the soil is determined and accordingly crops or plants are suggested that can be grown in the field. Due to detection of soil pH value, we can reduce the chances of crops being destructed.